Limnology and ecology of lakes along the Sôya Coast, East Antarctica - Kudoh, Sakae; Tanabe, Yukiko (Polar Research Institute of China - PRIC, 2014)
The Sôya Coast in East Antarctica has several ice-free areas where many small (<1 km2) and shallow (<50 m depth) glacial lakes display various limnological features. Geological, biological, and ecological studies conducted by the Japanese Antarctic Research Expeditions since 1957 are reviewed herein. Most of the lakes along the coast are oligotrophic; however, water quality is highly variable depending on differences in lake morphology and history. Geophysical and paleolimnological studies suggest that most of the lakes appeared after the Last Glacial Maximum (LGM) and have since maintained a lacustrine condition. The ubiquitous occurrence of benthic microbial assemblages with low phytoplankton biomasses is a common feature of other Antarctic lakes. However, diverse benthic assemblages such as moss pillars and large pinnacle microbial structures are found in the lake basins. Frequent and continuous limnological studies have revealed three typical water circulation patterns, underwater light climate features (too much light, which includes UV radiation during the ice free season), and the structure of benthic assemblages based on their photosynthetic physiology. The phenomenon of mass floatation of benthic assemblages was observed in a lake during the ice-covered season; this was explained by seasonal environmental conditions. Thus, a hypothesis was formulated based on ecological matter cycling, eutrophication, and lake succession processes.